Active and fossil hydrothermal zones of the Apacheta volcano: Insights for the Cerro Pabellón hidden geothermal system (Northern Chile). (November 2021) - Maza, Santiago N.; Collo, Gilda; Morata, Diego; Taussi, Marco; Vidal, Jeanne; Mattioli, Michele; Renzulli, Alberto
Highlights: Sulphate, clay, silica and oxide-hydroxide minerals from active and fossil hydrothermal area of the Cerro Apacheta volcano (Cerro Pabellón geothermal field, northern Chile) were identified for the first time. Mineral assemblages and their spatial distribution in the active zone allow defining S uperficial advanced argillic alteration facies associated with  Argillic alteration facies,  consistent with an acid-sulphate steam-heated environment. The presence and distribution of Mg-Zn-Cu rich montmorillonites and beidellites in the active and fossil zones are used as indicative of the hot mineralized vector fluids. The distribution of the hydrothermal alterations is likely related to the structural setting, linked to the Pabelloncito graben, a primary feature in the control of the circulation of hydrothermal fluids towards the surface. Mineralogical and geochemical data as well as structural setting made this area promising for further geothermal exploration studies in the northern Chile. Abstract: Sulphate, clay, silica and oxide-hydroxide minerals were identified by means of fieldwork, XRD and SEM, both in the active and fossil zones of the Cerro Apacheta volcano (Cerro Pabellón geothermal field, northern Chile). Mineral assemblages and their spatial distribution in the active zone allow defining S uperficial advanced argillic alteration facies associated with Argillic alteration facies, consistent with an acid-sulphate steam-heated environment. Poor crystallized kaolinite and cristobalite (opal-C), alunite in the steaming ground, alunogen and Mg-Zn-Cu-rich smectite in the fumarolic deposits represent the main mineralogical associations of this zone. The same two facies are defined in the fossil zone, interpreted as related to a superficial epithermal environment, with well crystallized kaolinite, alunite-natroalunite, pyrophyllite, mixed opal-A-opal C/T-quartz and Mg-Zn-Cu-rich Illite/Smectite (I/S). The presence and distribution of Mg-Zn-Cu rich montmorillonites and beidellites in the active and fossil zones are used as indicative of the hot mineralized vector fluids. In the active zone they would be interpreted alternatively as the result of an in situ argillic alteration, overlapping steam-heated typical assemblages and mineral associations formed in the fumarolic zones, or having an "allochthonous" origin, being formed at depth within the superficial part of the clay cap and subsequently transported to the surface during phreatic eruptions or fluidized events. The distribution of the hydrothermal alterations is likely related to the intersection of NW-SE and NE-SW structures, linked to the Pabelloncito graben, a primary feature in the control of the circulation of hydrothermal fluids towards the surface.